High-fat diet-induced increase in glucocorticoids contributes to adipogenesis in obese mice - Sheng-Feng Tsai; Pei-Ling Hsu; Mei-Chen Yeh; Hao-Chang Hung; Monica Meng-Chun Shih; Bon-chu Chung; Chia-Yih Wang; Chih-Jen Chang; Yu-Min Kuo (Biomedical Journal, 2025)
Background: This study was designed to examine how glucocorticoids (GCs) induced by a long-term ingestion of high-fat diet (HFD) mediate the HFD-induced adipose expansion and obesity. Material and methods: To address this goal, we used a unique L/L mouse model that fails to induce its corticosterone (CORT) level, a major type of GCs in rodents, after prolonged exposure to an HFD. Results: We found that, after receiving a 12-week HFD feeding, the L/L mice show less weight gain, milder adipose expansion, and higher plasma levels of triglycerides than the wild-type mice. These changes were reversed by replenishing CORT to L/L mice. When examining the expression levels of various molecules linked to lipid uptake and de novo lipogenesis in CORT-induced adipose expansion, we observed a reduction in the expression of adipose preadipocyte factor 1 (Pref-1), a key regulator in adipogenesis. In 3T3-L1 preadipocyte-like cells, dexamethasone, an agonist of the glucocorticoid receptor, also reduced expressions of Pref-1 and facilitated intracellular accumulation of lipids. Conclusions: Our results suggest that fat ingestion-induced release of CORT contributes to adipose expansion and development of obesity and highlight the pathogenic role of CORT-mediated downregulation of adipose Pref-1 in diet-induced obesity.